A comprehensive review on the effects of green tea and its components on the immune function - Jiachen Sun; Shengjie Dong; Jianying Li; Hui Zhao (Food Science and Human Wellness)
Green tea and its bioactive components possess many health-promoting and disease-preventing benefits, especially anti-inflammatory, antioxidant, anticancer, and metabolic modulation effects with multi-target modes of action. In contrast, the effects and mechanisms of tea and its components on the immune system are rarely reviewed. The study aimed to review the most potent compounds in tea that affect the immune systems and mechanisms associated with it. As a result of in vitro studies, animal models, and human trials, researchers have found that green tea extracts and compounds have the possibility of modulating the innate immune system, adaptive immune system, and intestinal immune system. In immune-related diseases, tea polyphenols are the most significant compounds that modify immune functions, though other compounds are being investigated and cannot be ruled out. The review provides a new perspective on how the immune-regulatory effects of tea and its components are exerted on immune systems, as well as how they affect the emergence and treatment of diseases.